Promoting sustainability through behavior change: A review. (November 2015) - Coskun, Aykut; Zimmerman, John; Erbug, Cigdem
Abstract : Over the last decade, the design research community has become increasingly interested in promoting more sustainable behaviors through the design of new products and services. We conducted a literature review to help advance this growing research area. The review characterizes the current state by identifying conceptual studies that proposed strategies, frameworks, toolkits, and guidelines for behavior change. It also documents empirical studies that investigate opportunities for behavior change by proposing novel artifacts that promote sustainable behaviors and evaluations of these artifacts through field studies. Our review identifies gaps including a lack of detail on how designers select target behaviors, users, and opportunities; research on topics other than electricity consumption and the domestic context; research that integrates behavior change strategies other than feedback; and longitudinal evaluations that demonstrate a lasting behavior change. Based on these gaps, we offer some priorities for future research. Highlights: We conducted a review on design for behavior change and sustainability. We characterized the current research, identified gaps and made recommendations for future work. Future work should identify the most promising areas where design can have a significant impact. It should identify behavior change strategies that have the most profound and lasting impact.